2002
DOI: 10.1111/j.1365-2621.2002.tb08760.x
|View full text |Cite
|
Sign up to set email alerts
|

Pasture and Grain Finishing Affect the Color Stability of Beef

Abstract: We determined the effect of pasture feeding (P0) or sorghum feeding with 2500 IU/head/d; (G2500) or without (G0) vitamin E supplementation on the color stability of gluteus medius (GM), longissimus lumborum (LL) and semimembranosus (SM). Diets did not affect the total pigment concentration of the muscle. Color stabilities were G2500 > P0 > G0 for fresh GM and SM and G2500 > G0 > P0 for fresh LL. Color stabilities of aged beef from the P0 and G2500 treatments were similar and higher than those from unsupplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 29 publications
4
12
2
3
Order By: Relevance
“…This result aligns with work by both Lanari et al (2002) and Yang et al (2002) who found supplemented cattle had a better colour stability than pasture fed animals. Different muscles may vary in initial colour due to differing pigment concentrations (myoglobin), associated with variation in fibre type (Gardner et al, 2007).…”
Section: Further Investigation Into Different Aging Periods and Vitamsupporting
confidence: 90%
See 1 more Smart Citation
“…This result aligns with work by both Lanari et al (2002) and Yang et al (2002) who found supplemented cattle had a better colour stability than pasture fed animals. Different muscles may vary in initial colour due to differing pigment concentrations (myoglobin), associated with variation in fibre type (Gardner et al, 2007).…”
Section: Further Investigation Into Different Aging Periods and Vitamsupporting
confidence: 90%
“…Many researchers have shown that aging of beef causes a faster deterioration of surface colour once on display (Lanari, Brewer, Yang & Tume, 2002;Liu, Scheller, Arp, Schaefer & Frigg, 1996;Lynch, Kerry, Buckley, Faustman & Morrissey, 1999).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There are differences in the diet effects on carcass and meat quality if the animals are slaughtered at different ages (same weight, but different growth rates) or at different weights (same age, and different growth rates), (PRIOLO et al, 2001). Grass feeding has reported to affect several carcass and meat quality characteristics, in particular colour and flavour (SCHWARZ et al, 1998;MUIR et al, 1998;PRIOLO et al, 2001;PURCHAS et al, 2002;YANG et al, 2002;LANARI et al, 2002;ARTHUR et al, 2004;HOLLO et al, 2004;SCHNAECKEL et al, 2006). However, FRENCH et al 2000 showed that when steers had a similar mean rate of carcass growth, pre-slaughter diet (autumn grazed grass, concentrates or grass silage) did not affect the sensory perception of meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Colour perception plays a major role in the evaluation of meat quality as consumers use the colour as an indicator of freshness and it strongly influences the consumer's purchase decision (Feldhusen et al 1995;Lanari et al 2002). During storage, distribution and display, the processes of oxygenation and oxidation of myoglobin influence colour (Mancini and Hunt 2005).…”
Section: Introductionmentioning
confidence: 99%